2022
DOI: 10.3389/fpls.2022.824240
|View full text |Cite
|
Sign up to set email alerts
|

microRNAs and Their Roles in Plant Development

Abstract: Small RNAs are short non-coding RNAs with a length ranging between 20 and 24 nucleotides. Of these, microRNAs (miRNAs) play a distinct role in plant development. miRNAs control target gene expression at the post-transcriptional level, either through direct cleavage or inhibition of translation. miRNAs participate in nearly all the developmental processes in plants, such as juvenile-to-adult transition, shoot apical meristem development, leaf morphogenesis, floral organ formation, and flowering time determinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
62
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(65 citation statements)
references
References 237 publications
(219 reference statements)
0
62
1
2
Order By: Relevance
“…In plants and animals, microRNAs (miRNAs) direct Argonaute (AGO) proteins to repress mRNA expression by inhibiting translation or marking the RNA for destruction (Chen, 2009; Bartel, 2018; Dong et al, 2022; Zhang et al, 2022). In animals, miRNA biogenesis begins in the nucleus with the excision of a pre-miRNA stem loop from a primary miRNA transcript by the ribonuclease III enzyme Drosha, aided by a partner protein with multiple double-stranded RNA-binding domains (dsRBDs) (Lee et al, 2003; Denli et al, 2004; Gregory et al, 2004; Han et al, 2004; Han et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In plants and animals, microRNAs (miRNAs) direct Argonaute (AGO) proteins to repress mRNA expression by inhibiting translation or marking the RNA for destruction (Chen, 2009; Bartel, 2018; Dong et al, 2022; Zhang et al, 2022). In animals, miRNA biogenesis begins in the nucleus with the excision of a pre-miRNA stem loop from a primary miRNA transcript by the ribonuclease III enzyme Drosha, aided by a partner protein with multiple double-stranded RNA-binding domains (dsRBDs) (Lee et al, 2003; Denli et al, 2004; Gregory et al, 2004; Han et al, 2004; Han et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…They exert a negative regulation on the expression of target genes through sequence-based complementarity, resulting in mRNA cleavage or translation repression ( Chen et al, 2015 ; Song et al, 2019 ; Wang M et al, 2021 ). Studies have shown that miRNAs play important roles in plant growth and development, including organ morphogenesis, hormone secretion, and stress response ( Aukerman and Sakai, 2003 ; Sunkar et al, 2012 ; Dong et al, 2022 ). For example, in Osmanthus fragrans , miR858 affects flavonoid content in flower tissues by negatively regulating the MYB1 gene ( Shi et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Some miRNAs are shown to function in chromatin modi cation by mediating DNA methylation and also regulate gene expression by targeting their promoters [3,4]. Plant miRNAs play key roles in almost all aspects of growth and development, ranging from embryogenesis, vegetative growth, organ formation, juvenile-to-adult transition, owering time determination and senescence and death [5][6][7].…”
Section: Introductionmentioning
confidence: 99%